If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + 8x = -6(2x + -3) Reorder the terms: 22 + 8x = -6(-3 + 2x) 22 + 8x = (-3 * -6 + 2x * -6) 22 + 8x = (18 + -12x) Solving 22 + 8x = 18 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 22 + 8x + 12x = 18 + -12x + 12x Combine like terms: 8x + 12x = 20x 22 + 20x = 18 + -12x + 12x Combine like terms: -12x + 12x = 0 22 + 20x = 18 + 0 22 + 20x = 18 Add '-22' to each side of the equation. 22 + -22 + 20x = 18 + -22 Combine like terms: 22 + -22 = 0 0 + 20x = 18 + -22 20x = 18 + -22 Combine like terms: 18 + -22 = -4 20x = -4 Divide each side by '20'. x = -0.2 Simplifying x = -0.2
| 24x^2=24w-6 | | 3(5+3m)=42 | | r(r+5)-104=0 | | 7x+7+14+110=180 | | 37-10a=51+6a | | 2(3x-1)=2x+10 | | x(3x-1)=310 | | 9(7-2x)=12(2+5) | | 3x*2+23x-8=0 | | 2x/3=(x/6)+1 | | 4u^3w^4/2u^4y^3-10u^2 | | (-6.8)+(-1.9)= | | -9k+4+7k=23 | | 1/3(9x+14)+1/3 | | (-1)+11+5= | | ln(3n+7)=ln(-3n-5) | | x^2-x-8=65 | | (B-2)+(B)+(B*4)=26 | | y=1/2*4.5+4 | | (x+3)(x-3)-40=0 | | y=1/2x*4.5+4 | | 20/3^2+4-2^3 | | -3(-1)(-2)(5)= | | y^2+12=-64 | | x^2-5x=66 | | 2x+x-10=0 | | -2x-8=-15x^2 | | 0.33f-6=-8 | | -3(a+3)-6=2(4a+5)+8 | | (x+3)(x-3)-16=0 | | (B-2)+(B)+(B+3)=25 | | 6-1/4=C |